Analisis Struktur Naratif Prosa Digital Terhadap Bentuk dan Pola Cerita Dear J Karya Lilac Lulabby Di Platform Wattpad - Nadila Saritri; Sovia Wulandari; Siti Fitriah; Anggi Triandana (Universitas Batanghari Jambi, 2026)
This study aims to analyze the story structure in digital prose titled Dear J written by Lilac Lullaby on the Wattpad platform, utilizing the structural narratology approach of Gérard Genette and transmedial narratology by Marie-Laure Ryan. The method applied is descriptive qualitative, with data collection techniques including text quotations and screenshot documentation. The research findings indicate that the narrative structure is dominated by anachronic patterns (analepsis) that have variations in duration such as summaries, scenes, and pauses, coupled with iterative and repetition frequencies. The use of internal focalization and a homodiegetic narrator also strengthens the narrative delivery. In addition, the features on Wattpad have an impact on the formation of the narrative through the concepts of cross-media narrative, interactivity, multimodality, seriality, and fragmentation. The narrative is not only presented in written form, but also involves reader interaction through the features on the platform. Thus, the narrative develops through the relationship between text, media, and reader participation.